Hot press as a sustainable direct recycling technique of aluminium: mechanical properties and surface integrity - Yusuf, Nur Kamilah; Lajis, Mohd Amri; Ahmad, Azlan (MDPI, 2017)
Meltless recycling technique has been utilized to overcome the lack of primary resources, focusing on reducing the usage of energy and materials. Hot press was proposed as a novel direct recycling technique which results in astoundingly low energy usage in contrast with conventional recycling. The aim of this study is to prove the technical feasibility of this approach by characterizing the recycled samples. For this purpose, AA6061 aluminium chips were recycled by utilizing hot press process under various operating temperature (Ts = 430, 480, and 530 °C) and holding times (ts = 60, 90, and 120 min). The maximum mechanical properties of recycled chip are Ultimate tensile strength (UTS) = 266.78 MPa, Elongation to failure (ETF) = 16.129%, while, for surface integrity of the chips, the calculated microhardness is 81.744 HV, exhibited at Ts = 530 °C and ts = 120 min. It is comparable to theoretical AA6061 T4-temper where maximum UTS and microhardness is increased up to 9.27% and 20.48%, respectively. As the desired mechanical properties of forgings can only be obtained by means of a final heat treatment, T5-temper, aging after forging process was employed. Heat treated recycled billet AA6061 (T5-temper) are considered comparable with as-received AA6061 T6, where the value of microhardness (98.649 HV) at 175 °C and 120 min of aging condition was revealed to be greater than 3.18%. Although it is quite early to put a base mainly on the observations in experimental settings, the potential for significant improvement offered by the direct recycling methods for production aluminium scrap can be clearly demonstrated. This overtures perspectives for industrial development of solid state recycling processes as environmentally benign alternatives of current melting based practices.